Graphite, graphene on SiC, and graphene nanoribbons: Calculated images with a numerical FM-AFM - Castanié, Fabien; Nony, Laurent; Gauthier, Sébastien; Bouju, Xavier (Beilstein Journal of Nanotechnology, 2012)
Background: Characterization at the atomic scale is becoming an achievable task for FM-AFM users equipped, for example, with a qPlus sensor. Nevertheless, calculations are necessary to fully interpret experimental images in some specific cases. In this context, we developed a numerical AFM (n-AFM) able to be used in different modes and under different usage conditions.Results: Here, we tackled FM-AFM image calculations of three types of graphitic structures, namely a graphite surface, a graphene sheet on a silicon carbide substrate with a Si-terminated surface, and finally, a graphene nanoribbon. We compared static structures, meaning that all the tip and sample atoms are kept frozen in their equilibrium position, with dynamic systems, obtained with a molecular dynamics module allowing all the atoms to move freely during the probe oscillations.Conclusion: We found a very good agreement with experimental graphite and graphene images. The imaging process for the deposited nanoribbon demonstrates the stability of our n-AFM to image a non-perfectly planar substrate exhibiting a geometrical step as well as a material step.
Keywords: calculations; FM-AFM; graphene; graphite; image; nanoribbon